1990
DOI: 10.1080/01635589009514050
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime alcohol intake and risk of rectal cancer in western New York

Abstract: The lifetime intake of total alcohol, beer, wine, and hard liquor was measured for 277 males and 145 females with pathologically confirmed, first, single, primary cancers of the rectum in western New York from 1978 to 1986. Controls who were age, sex, and neighborhood matched were also interviewed. Intake of beer and total alcohol was positively associated with rectal cancer risk. Most of the excess risk was found for the heaviest drinkers. Odds ratios for fourth quartile intakes for males were 1.80 (95% CI, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
3
19
1
Order By: Relevance
“…11,15,16,19,25,41 Similarly, most epidemiologic studies report stronger associations between alcohol and CRC for men when compared with women. 15,19,39,41 Our data however, showed no interaction between alcohol consumption and sex, and an additional stratification of our analyses showed similar results for men and women. In addition to the large meta-analyses, [5][6][7]50 the Pooling Project 4 and the EPIC study, 8 we did not observe any evidence for sex-specificity.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…11,15,16,19,25,41 Similarly, most epidemiologic studies report stronger associations between alcohol and CRC for men when compared with women. 15,19,39,41 Our data however, showed no interaction between alcohol consumption and sex, and an additional stratification of our analyses showed similar results for men and women. In addition to the large meta-analyses, [5][6][7]50 the Pooling Project 4 and the EPIC study, 8 we did not observe any evidence for sex-specificity.…”
Section: Discussionsupporting
confidence: 56%
“…The majority of individual casecontrol [10][11][12]39,[41][42][43][44][45] and cohort studies [14][15][16]18,25,40,[46][47][48][49] have shown rather inconsistent results, which in part can be explained by differing (methodological) aspects of these studies and lack of statistical power. To the best of our knowledge, our study is currently the largest single prospective study that has investigated associations between alcohol consumption and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of several earlier investigations (Sundby, 1967;Hakulinen et al, 1974;Nicholls et al, 1974;Monson & Lyon, 1975;Graham et al, 1978;Hirayama, 1979;Jensen, 1979Jensen, , 1980Robinette et al, 1979;Klatsky et al, 1981Klatsky et al, , 1988Schmidt & Popham, 1981;Manousos et al, 1983;Kono et al, 1986;Potter & McMichael, 1986;Tuyns, 1988). Our study thus does not support the alleged association between alcoholic beverages (Wynder & Shigematsu, 1967;Pickle et al, 1984;Hirayama, 1989;Carstensen et al, 1990;Freudenheim et al, 1990;Longnecker, 1990) including beer (Wynder & Shigematsu, 1967;Miller et al, 1983;Pollack et al, 1984;Kabat et al, 1986;Kune et al, 1987;Carstensen et al, 1990;Freudenheim et al, 1990) and the development of rectal cancer in particular. Owing to the size of the present study the relative risk estimate of 1.0 is quite precise, and it is unlikely that these heavy alcoholics have a more than 30% increased risk.…”
Section: Discussioncontrasting
confidence: 50%
“…Among these, five studies [41,67,68,76,82] were totally negative, and showed no evi dence of association with any of the large bowel subsites, sex strata or type of alcohol beverages. Three others showed overall signif icant direct associations, one [71] between beer and rectal cancer (RR = 2.7 for the high est consumption level), one [74] between total alcohol consumption and again rectal cancer only, but with RR estimates below 2 in both sexes. Both studies were conducted in North America.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Some North American studies [71,74,75,83] and an Australian one [72] found elevated risks, but were not confirmed by oth er studies from Europe, including one from Belgium [73] where beer is the commonest alcoholic beverage. This may suggest that dif ferent correlates of beer drinking in various populations may account for some of the ele vated risks, rather than supporting a general carcinogenic effect of beer itself on the rectal epithelium.…”
Section: Case-control Studiesmentioning
confidence: 99%